1993
DOI: 10.1111/j.1365-3040.1993.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of high temperature and elevated carbon dioxide concentration on cowpea [Vigna unguiculata(L.) Walp.]

Abstract: Limitations in carbohydrate supplies have been implicated as a factor responsible for reproductive failure under heat stress. Heat stress affects two stages of reproductive development in cowpea [Vigna unguiculata (L.) Walp.], and genotypes are available with tolerance and sensitivity to heat during these different stages. The objectives of this study were to determine the responses of these cowpea lines to ambient and elevated [CO2], under heat stress and optimal temperature, and test whether differences in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(46 citation statements)
references
References 29 publications
1
43
2
Order By: Relevance
“…montana), whose presence is limited in the northern states by winter low temperatures (Bunce and Ziska 2000). Alternatively, greater increases in summer night-time relative to day-time temperatures projected with global warming (McCarthy et al 2001) could decrease seed production to a greater extent in crop relative to weed species (e.g., cowpea, Vigna unguiculata, Ahmed et al 1993) with subsequent competitive effects. Differential responses of seed emergence to temperature could also influence species establishment and subsequent weed/crop competition (e.g., Houghton and Thomas 1996).…”
Section: Climate Effects On Ecology and Distributionmentioning
confidence: 99%
“…montana), whose presence is limited in the northern states by winter low temperatures (Bunce and Ziska 2000). Alternatively, greater increases in summer night-time relative to day-time temperatures projected with global warming (McCarthy et al 2001) could decrease seed production to a greater extent in crop relative to weed species (e.g., cowpea, Vigna unguiculata, Ahmed et al 1993) with subsequent competitive effects. Differential responses of seed emergence to temperature could also influence species establishment and subsequent weed/crop competition (e.g., Houghton and Thomas 1996).…”
Section: Climate Effects On Ecology and Distributionmentioning
confidence: 99%
“…In some studies of floral abortion under temperature stress, the observed reduction in carbohydrate supply to the reproductive tissues was attributed rather to reduction in sink demand (e.g. abscission of reproductive structures) than to assimilate supply by photosynthetic tissues in tomato (Dinar and Rudich, 1985), pepper (Aloni et al, 1991), and cowpea (Vigna unguiculata L.) (Ahmed et al, 1993). Thus, without neglecting the importance of vegetative growth as the source of nutrients and reserves for sink reproductive structures, it seems that small temperature fluctuations -in magnitude and span-that do not necessarily result in great effects on vegetative growth and photosynthetic activity, could be a limiting factor for the likelihood of a flower to set seeds.…”
Section: Flowering Stage Sensitivity To Temperature Fluctuationsmentioning
confidence: 99%
“…Genetic diversity for heat tolerance has already been demonstrated for crops such as wheat [124], soybean [125], peanut ( [126,127], Table 2), bean [128], cowpea [129], and cotton [130]. Breeders could also consider incorporating photoperiod insensitivity [131] so that seed filling can begin before the onset of the highest temperatures [132].…”
Section: Plant Breedingmentioning
confidence: 99%